MANAGEMENT OF DADRU KUSHTHA THROUGH AYURVEDA – A CASE REPORT - Gautam, Apeksha; yadav, sarika; C.R Yadav (International Research Journal of Ayurveda & Yoga, 2024)
Skin being the largest and a protective covering of all our internal organs is susceptible to many harmful environmental factors causing different kinds of bacterial, viral and fungal infections. All the skin disease in Ayurveda has been classified into Mahakushtha and Kshudra Kushtha. Dadru is one among them. As per modern perspective “Superficial fungal infection of skin” is the most common dermatological manifestation affecting up to 15% of world‟s population in all age groups. In present time, antifungal treatment is based on systemic and topical medications which may lead to many side effects and relapse too. Fungal infections are more demoralizing to the patients due to their appearance, recurrence, chronicity, and negative psychological impact. Keeping this fact in mind below mentioned study drafted to focuses on Ayurvedic Shamana and Shodhan Chikitsa in Dadru Kushtha. AIM AND OBJECTIVES –To evaluate the effect of Shodhana and Shamana Chikitsa in Dadru Kushtha. MATERIAL AND METHODS- It will be collected from classical Ayurvedic texts as well from previous research works / thesis, Internet sources, research articles and modern sciences text. DISSCUSSION AND CONCLUSIONS- On the basis of signs and symptoms we can correlated the Dadru Kushtha to Tinea Cruris. In This case report, a 67 yr old male patient came with complaints of Dadru Kushtha, which is closely similar to the presentation of Tinea Cruris infection. The present case showed significant improvement with Ayurvedic Shodhan, Shaman and Bahiparimarjan (topical) Chikitsa in Dadru.